THE EFFECT OF KNOWLEDGE OF ETHICS, RELIGIOSITY, ETHICAL SENSITIVITY, ETHICAL ORIENTATION TO ACCOUNTING STUDENTS PERCEPTION OF CREATIVE ACCOUNTING PRACTICES - Dede Sevi; Sri Mulyati; Asep Kurniawan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2021)
Creative accounting is an ethical dilemma because it does not seem to violate the rules but causes users of financial statements to make wrong decisions. With the occurrence of various accounting scandals abroad and in Indonesia that has committed creative accounting actions, it is evident that there are still many accountants who violate the basic principles of professional accounting ethics and from creative accounting actions that have resulted in companies collapsing. This study aims to examine whether there is a relationship between ethical knowledge, religiosity, ethical sensitivity, and ethical orientation to accounting students' perceptions of creative accounting practices. The subjects of this study were students of higher education accounting study programs in West Java. The research method used in this research is quantitative with a questionnaire. The survey was conducted on 320 respondents of higher education accounting students in West Java. The analysis technique uses multiple linear regression analysis with SPSS software. The results of this study indicate that: ethical knowledge has a positive effect on accounting students' perceptions of creative accounting practices, religiosity does not affect accounting students' perceptions of creative accounting practices, ethical sensitivity has a positive effect on accounting students' perceptions of creative accounting practices, ethical orientation does not affect perceptions. accounting students regarding creative accounting practices. And simultaneously ethical knowledge, religiosity, ethical sensitivity, and ethical orientation affect the perceptions of accounting students regarding creative accounting practices as evidenced by the F value of 62.587> F table 2,4003 and a significance value of 0,000 <0.05.